Case Report: Spectrum of interesting ocular manifestations following COVID-19 vaccination: a case series of real-world presentations - Tajunisah, Iqbal; Tan, Shao Sze; Effendi-Tenang, Irina; Samsudin, Amir; Ling, Kiet-Phang; Tan, Wee Yong; Ramasamy, Sunder; Fong, Kenneth Choong Sian (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose: We report the ocular findings of patients which occurred after receiving coronavirus disease 2019 (COVID-19) vaccination in three different eye centers in Malaysia. Observations: A total of four cases were reported. Three patients received Pfizer-BioNTech vaccine while the other received Oxford Astra-Zenaca type. Ocular symptoms occurred after the first vaccine dose in two patients and after 2 the second vaccine dose in the other two. Three out of four patients required active treatment for their vision complications post-vaccination. The first patient had acute onset retinal pigment epitheliitis within three hours of vaccination and was treated conservatively. The second patient developed unilateral choroidal neovascularization three days after vaccination and required intravitreal antivascular endothelial growth factor injection. The third patient presented with bilateral acute multifocal placoid pigment epitheliopathy a week after vaccination, that responded to intravenous methylprednisolone. The fourth patient presented with herpes zoster infection and unilateral anterior nongranulomatous uveitis two weeks after vaccination and was treated with oral acylovir and topical corticosteroids. All patients reported some amount of visual recovery. Conclusions and Importance: Visual symptoms and various ocular adverse events can occur following COVID-19 vaccination, which warrant further investigation and urgent intervention if necessary. We would suggest patients receiving COVID-19 vaccination to be aware of possible ocular complications and to report any symptoms, regardless of severity.